Changes on microbial C and enzyme activities in soil with amendment of composted tannery sludge after 9 years - Antonio Victor Cavalcante Rocha Silva; Francisco Barbosa De Macedo Junior; Jadson Emanuel Lopes Antunes; JoÃ£o Pedro Alves De Aquino; Regina Maria Silva Sousa; Louise Melo De Souza Oliveira; Ademir SÃ©rgio Ferreira De Araujo (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The consecutive amendment of composted tannery sludge (CTS) could promote changes in the status of soil microorganisms. Thus, this study evaluated the changes on microbial C and enzyme activities in soil after 9 years of CTS amendment. Methods CTS was amended from 2009 to 2018 at five rates: 0, 2.5, 5, 10, and 20 ton haâ1. In 2018, the soil chemical properties (pH, electric conductivity, P, K, Cr, and total organic C), microbial C and enzyme activities were evaluated after 30 days from the amendment. Results The values of chemical properties increased after nine years of CTS application. The content of microbial C and the enzyme activities increased with the amendment of 2.5 and 5 ton haâ1, and decreased with the amendment of10 and 20 ton haâ1. Conclusion This study showed that the amendment of10 and 20 ton haâ1 of CTS increased soil pH and Cr concentration and promoted a decreasing on soil microbial C and enzyme activities.